Significant Role of MUC1 in Development of Resistance to Currently Existing Anti-cancer Therapeutic Agents - Farahmand, Leila; Merikhian, Parnaz; Jalili, Neda; Darvishi, Behrad; Majidzadeh-A, Keivan (Current Cancer Drug Targets, 2018)
As an extensively glycosylated transmembrane protein of epithelium, Mucin1 (MUC1) mostly protects cells from tensions induced by external milieu. Physiologically, during stress condition, MUC1 separates into MUC1-N and MUC1-C moieties, resulting in transduction of inward survival signals, essential for maintaining cell's functionality. Recent studies have proposed a significant correlation between MUC1 overexpression and amplification of cancer cell's proliferation and metastasis through modulation of multiple signaling pathways and cell-cell and cell-matrix interactions. It has been shown that MUC1- Cytoplasmic Domain (MUC1-CD) accelerates development of resistance to several anti-cancer therapeutic agents including bortezomib, trastuzumab and tamoxifen. Furthermore, MUC1-CD is also involved in promoting expression of multi drug resistance (MDR) genes and finally, silencing MUC1 expression was together with resensitization of human epidermal growth factor receptor 2 positive (HER2+) and/or estrogen receptor (ER+) positive breast cancer cells to bortezomib, trastuzumab and tamoxifen respectively. In this review, we briefly describe the role of MUC1 proto-oncogene in cancer cell's survival, tumor progression and metastasis and then continue with mentioning the mechanisms through which MUC1 induce resistance to various currently existing therapeutic agents in market including bortezomib, trastuzumab and tamoxifen.
Keywords: cancer propagation